Clinico-genomic study reveals association of dengue virus genome high frequency mutations with dengue disease severity - Varsha Ravi; Md Imran; Kriti Khare; Pallavi Mishra; Ramakant Mohite; Kanika; Md Abuzar Khan; Aparna Swaminathan; Aanchal Yadav; Sristi Sinha; Richa Shukla; Partha Chattopadhyay; et al. (Scientific Reports)
Abstract Transmission of the dengue virus (DENV) places a huge burden on public health in several endemic regions. Like other RNA viruses, mutations in the DENV genome greatly governs its virulence, transmissibility, and interaction with the host immune system. Present study focuses on integrated analysis of mutation and clinical data accompanied at the onset of dengue fever. The findings from the associated clinical data with the variants of the DENV are critical for early detection of the disease and understanding the disease progression. RNA was isolated from the 1310 serum samples collected from the NS1-antigen positive dengue patients. Serotyping reveals that DENV-2 was predominant in circulation. The genome of 1305 DENV-2 was sequenced using Oxford Nanopore Technology and Illumina platforms. A total of 1023 DENV-2 demonstrated > 50% genome coverage. Mutation analysis across the 1023 DENV-2 genomes yielded a total of 2667 mutations including 627 non-synonymous and 2040 synonymous mutations. We observed a notable over-representation of synonymous mutations in prM and ancC genes while a higher occurrence of non-synonymous mutations was found in ancC, prM, and M proteins. Comparison of mutation frequency between mild and severe demonstrates higher mutation frequency in severe phenotype. Moreover, we observed a total of 56 significant mutations including 23 in severe, 17 in moderate and 16 in mild. The E-protein having non-synonymous mutations were docked with DC-SIGN with lower binding energy (ΔG = − 11.9 kcal/mol) for severe as compared to mild (ΔG = − 13.5 kcal/mol), suggesting lesser affinity of E-protein and DC-SIGN in case of severe as compared to the mild. We have identified the core set of high frequency mutations significantly associated with distinct dengue disease severity viz., mild, moderate and severe. Furthermore, in-silico protein modelling and docking studies demonstrate the potential functional role of the non-synonymous mutations identified across E-protein in severe dengue.